Detection of Trypanosoma brucei by microwave cytometry - Jeffrey A. Osterberg; Jillian Milanes; James Morris; Pingshan Wang (Sensors and Actuators Reports, 2022)
Researchers studying cellular life cycles need to be able to monitor the phases of a cell cycle rapidly and accurately. Many of the techniques currently used to monitor the cell cycle require the use of labels and would be difficult to automate. Microwave cytometry is a promising new approach to label free monitoring of cell life cycles. This paper presents results of multiple frequency microwave measurements of two lifecycle stages of Trypanosoma brucei, a unicellular eukaryotic parasite found in sub-Saharan Africa. A microwave flow cytometer was used to show bloodstream form (BSF) and procyclic form (PCF) T. brucei have frequency dependent permittivity and impedance from 800 MHz to 7.65 GHz. The two cell forms had a strong dependence on the imaginary part of permittivity at 2.38 GHz and below and a strong dependence on the real part of permittivity at 5.55 GHz and above. Three PCF cell lines were tested to verify that the differences between the two cell forms were independent of cell strain. Additionally, impedance measurements were used to improve cell classification in cases where the permittivity of a cell cannot be detected. Quadratic discriminate analysis was employed to validate the ability to classify cells forms, with maximum cross-validation errors of 15.4% and 10% when using one and three PCF strains, respectively.